Effect of crop rotation with grain pearl millet on Pratylenchus penetrans and subsequent potato yields in Quebec - Dauphinais, Nathalie; Bélair, Guy; Fournier, Yvon; Dangi, Om (Phytoprotection, 2005)
AbstractA field study was conducted in Quebec to determine the effect of crop rotation with grain pearl millet (Pennisetum glaucum) on Pratylenchus penetrans populations and the subsequent yields of two potato cultivars (Solanum tuberosum) when compared with rye and continuous potato with and without fumigation. Pearl millet had a suppressive effect on P. penetrans populations compared with rye but not as much as continuous potato with fumigation. In 2002, total potato yields of cv. Superior and cv. Hilite Russet were negatively correlated with P. penetrans densities at harvest. Total yields of potato cv. Superior were increased by 123 and 229% following pearl millet and fumigation, respectively, compared with rye. Total yields of potato cv. Hilite Russet increased by 26 and 17% following pearl millet and fumigation. Grain pearl millet CGPM H-1 reduced P. penetrans densities and improved potato yields in Quebec.